KAJIAN KANDUNGAN SENYAWA PHENOL DAN SENYAWA PAH PADA ASAP CAIR CANGKANG KELAPA SAWIT (ACCKS) REDESTILASI YANG DIHASILKAN PADA TEMPERATUR TINGGI - Desi Ardilla; Muhammad Thamrin; Basuki WS; Eddiyanto , (AGRIUM: Jurnal Ilmu Pertanian, 2013)
Pyrolysis process is carried out in this study using a furnace, the temperature is set ranging from 600,700,800,900 ᵒ C using condenser cooling spiral type. Liquid smoke oil palm shell (ACCKS) produced centrifuge with speed 380 rpm for 30 min, filtered through filter paper and distilled at a temperature of 125 ᵒ C for 20 minutes ACCKS redestilasi analyzed the content of the compound phenol compound and polycyclic aromatic hydrocarbons (PAH) using a GCMS.To temperatures of 600 to 900ᵒC was not identified PAH compounds and the higher the temperature the lower the phenol compounds whereas the higher acetic acid compounds.Keuwords: ACCKS redestilation, phenol content, PAH, quality